Factors Affecting The Quality Of People With HIV / AIDS (PLWHA) Undergoing ARV Therapy - Iva Gamar Dian Pratiwi; Zakiyah Yasin (Universitas Muhammadiyah Semarang, 2021)
The incidence of HIV / AIDS is still high and is still described as an iceberg phenomenon. This condition forces PLWHA to always feel worried about their lives because they are threatened with death. The problems of PLWHA in Sumenep Regency are very complex, starting from the quality of life, stigma against PLWHA, transmission, treatment, to PLWHA, which until now have not been detected, coupled with the cultural atmosphere of the Madurese community, especially Sumenep Regency. This study aims to determine the factors that affect the quality of life of PLWHA undergoing ARV therapy. This type of research uses a survey design and is a quantitative study. The study population was all PLHIV patients who were actively using ARV therapy in Sumenep Regency, with a total sample of 56 respondents. Purposive sampling is used as a sampling technique. The independent variables in this study were socio-demographic factors (marital status, gender, age, education, occupation), medication adherence, duration of ARV therapy and stigma. The dependent variable is the quality of life. Chi-square test was used to test bivariate analysis and path analysis with the help of AMOS software was used to test multivariate analysis. The research location is in Sumenep Regency, namely in four Puskesmas which are used as ARV drinking facilities. In this study, it was found that the variable data that had the most influence on the quality of life was gender with a Nilai p of 0.055 which was smaller than α (0.1). The cross-tabulation analysis showed that female ODHA respondents had at least a good quality of life, namely only 14.3%. This is not surprising if this happens in Sumenep Regency, because from a cultural perspective, the Madurese are still very thick with their culture and local wisdom, where women are still in a subordinative position. Women with HIV / AIDS will be stigmatized and excluded from society.